Welcoming (and Learning from) the Stranger: The Museum as a Forum for Interfaith Dialogue. (2nd January 2019) - Williams, Ray
ABSTRACT: In response to current tensions around U.S. immigration policies and the expression of diverse religious identities, the author presents a case study in which a university art museum engaged local children and adults to share images and stories of their experience as practitioners of five of the world's major religions. These contemporary, local perspectives were presented through an exhibition combining ritual objects with documentary photographs; public performances of stories; and curricular resources designed to support middle school teachers in introducing Judaism, Hinduism, Buddhism, Christianity, and Islam. The case study shows how museums with collections of ritual objects can activate them on behalf of society's urgent need for interfaith dialogue and understanding to contribute to a more just and generous world.